Diseño de una red inalámbrica de telecomunicaciones para brindar servicios de telemedicina en las unidades de salud pública del cantón arenillas. - Cueva Rojas, Denis Alexander (2015)
In the present work it is realized the “Design of a wireless Telecommunications network to offer telemedicine services in the Public Health Units of the Arenillas city”; for which we begin with a study of the general concepts about the technological aspects and of the Health that includes the Telemedicine field, which will sustain a theoretical base for the project development. Furthermore it deals with a general overview of the state of the Telemedicine in Ecuador. This is performed in the chapter one. In the chapter two is realized a study to determine the wireless technology most adapted for this type of network underline technical aspects like functioning, ways of operation, etc, establishing fundamental technical requisites for the later selection of the appropriate teams. In the third and fourth chapter there is realized the design of the network as such for which to analyze the current situation of the Units of Health was a task of big importance to determine the bankruptcies as for telecommunications services and to realize an analysis of that one allows us a general vision of the requests in these health centers. To divide this, the design of the network is executed raising all the technological requests that this bears. In the fifth chapter there is prepared an analysis of the costs that bears this system for a future implementation, an analysis is realized as for necessary infrastructure and technological equipment. Finally an analysis is performed and discussion of results obtained later to prepare and to present the conclusions and recommendations that were obtained of this project.